2022
DOI: 10.3389/fgene.2022.960954
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis of the Tumor Microenvironment in Liver Metastasis of Colorectal Cancer Identified FJX1 as a Novel Biomarker

Abstract: Colorectal cancer incidence and mortality have increased in recent years, with more than half of patients who died of colorectal cancer developing liver metastases. Consequently, colorectal cancer liver metastasis is the focus of clinical treatment, as well as being the most difficult. The primary target genes related to colorectal cancer liver metastasis were via bioinformatics analysis. First, five prognosis-related genes, CTAG1A, CSTL1, FJX1, IER5L, and KLHL35, were identified through screening, and the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that levels of IER5L expression were increased in both primary tumor tissues and metastatic tumor tissues and were negatively correlated with survival. 20 , 21 Our study showed that IER5L expression was upregulated in many kinds of tumors in various systems and was associated with UICC stages and prognosis. Thus, in combination with the previous findings, we could conclude that IER5L may be a diagnostic and prognostic biomarker in cancer.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous studies have shown that levels of IER5L expression were increased in both primary tumor tissues and metastatic tumor tissues and were negatively correlated with survival. 20 , 21 Our study showed that IER5L expression was upregulated in many kinds of tumors in various systems and was associated with UICC stages and prognosis. Thus, in combination with the previous findings, we could conclude that IER5L may be a diagnostic and prognostic biomarker in cancer.…”
Section: Discussionmentioning
confidence: 72%
“… 20 Moreover, a growth on IER5L expression has been reported in metastatic colorectal cancer compared with primary cancer, and is negatively correlated with survival. 21 However, there are few pan-cancer analyses of IER5L and reports on the role of IER5L in NSCLC, so this study aimed to perform a pan-cancer analysis of IER5L and evaluate its value as a prognostic biomarker and a potential immunotherapeutic target for NSCLC.…”
Section: Introductionmentioning
confidence: 99%